Transformasi Praktik Jual Beli dalam Ekonomi Digital: Analisis Maqāṣid al-Sharī‘ah terhadap Perilaku Transaksi Perempuan Aceh di Media Sosial - Laila Mufida Laila; Munawar Ishak; Agustinar; Dessy Asnita (el-Amwal, 2026)
This study examines the transformation of Islamic buying and selling practices in the digital economy, focusing on social media-based transactions conducted by Acehnese women. In Aceh, where Islamic law is formally implemented, social media has become a prominent marketplace facilitating various commercial activities. However, digital transactions raise critical concerns regarding compliance with Islamic commercial principles, including contractual clarity, fairness, transparency, and the avoidance of gharar. Employing a qualitative approach with virtual ethnography, this study collects data through social media observation and in-depth interviews with Acehnese women actively engaged in digital transactions. The analysis applies the maqāṣid al-sharī‘ah framework to evaluate the conformity of these practices with Islamic commercial objectives. The findings indicate that most social media-based transactions rely on implicit, unwritten contracts, with varying levels of Sharia literacy among participants. While elements of mutual consent and price agreement are generally present, information asymmetry and potential gharar remain challenges. From a maqāṣid perspective, digital buying and selling practices are considered valid when they promote wealth protection, justice, and public benefit. This study underscores the importance of strengthening Islamic commercial literacy to ensure ethical and sustainable digital trade practices.